Delinquency prevention for individual change: Richard Clarke Cabot and the making of the Cambridge-Somerville Youth Study. (September 2017) - Welsh, Brandon C.; Zane, Steven N.; Rocque, Michael
Abstract: Purpose: Richard Clarke Cabot (1868–1939) designed and directed one of criminology's most well-known delinquency prevention programs and the field's first randomized controlled experiment: the Cambridge-Somerville Youth Study (CSYS). This paper aims to develop an historical understanding of the making of the CSYS through a focus on Cabot. Methods: The present study is guided by the socio-historical approach and informed by past historical research in criminology. It draws upon a wide array of archival records and published works from the late 19th century to present day. Results: The CSYS came to fruition through a culmination of personal, professional, and institutional influences on Cabot, including: his ideals and sense of pragmatism, refined by his transition from medicine to social ethics and social work; criminological luminaries in the 1920s and 1930s, who focused on the individual over the environment—most notably, William Healy and Augusta Bronner and Sheldon and Eleanor Glueck; and Cabot's concern with the failures of treatment of offenders. Conclusions: The study's early history and its lineage to Joan McCord's research on the study allows us to discern some of its legacies for delinquency prevention today, including application of the experimental design and a holistic view of delinquency prevention. The CSYS continues to have an influence on criminological thinking and research. Highlights: The Cambridge-Somerville Youth Study is criminology's first randomized experiment. Richard Cabot, a professor of medicine and social ethics, designed/directed the study. Personal, professional and institutional influences on Cabot led to the study. Joan McCord's research on the study is instrumental to the study's legacy. The study continues to have an influence on criminological thinking and research.